2011
DOI: 10.1027/0269-8803/a000030
|View full text |Cite
|
Sign up to set email alerts
|

The P3 Event-Related Potential as an Index of Motivational Relevance

Abstract: Watching motivationally relevant pictures modulates two types of event-related brain potentials (ERPs), the early posterior negativity (EPN) and the P3. Several studies show that the EPN and P3 to emotional stimuli are enhanced as compared to neutral stimuli. The goal of the present study was to investigate whether experimentally conditioned abstract stimuli (Gabor patches) that predict the occurrence of a subsequent emotional event are able to elicit an enhanced EPN and P3. This would confirm that these ERP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…Ideally, the design would more carefully balance image valence across categories. However, this imbalance is not problematic per se, given that late positive components of the ERP, such as the P3, are assumed to be modulated by the motivational significance of the stimulus, not by its valence (Begleiter et al., ; Franken et al., ; Weinberg and Hajcak, ; Weinberg et al., ). Indeed, ancillary analyses of the current data indicated that although positive images elicited a larger P3 overall than negative images, this effect did not vary systematically across picture categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the design would more carefully balance image valence across categories. However, this imbalance is not problematic per se, given that late positive components of the ERP, such as the P3, are assumed to be modulated by the motivational significance of the stimulus, not by its valence (Begleiter et al., ; Franken et al., ; Weinberg and Hajcak, ; Weinberg et al., ). Indeed, ancillary analyses of the current data indicated that although positive images elicited a larger P3 overall than negative images, this effect did not vary systematically across picture categories.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in ACR were quantified using the amplitude of the P3 (or P300) component of the event‐related potential (ERP). The P3 is elicited by any attended stimulus (see Polich, ), and its amplitude provides a neurophysiological marker of the motivational significance of that stimulus (e.g., Begleiter et al., ; Franken et al., ; Nieuwenhuis et al., ). Its etiologic relevance for AUD has been demonstrated by research showing that P3 amplitude elicited by alcohol cues (ACR‐P3) is a robust predictor of alcohol use and heavy drinking (e.g., Bartholow et al., ; Little et al., ).…”
Section: Overview Of the Current Study And Hypothesesmentioning
confidence: 99%
“…While it might seem surprising that this difference exists among non-smokers, our findings are consistent with ERP (Bloom, Potts, Evans, & Drobes, 2013; McDonough & Warren, 2001), fMRI (Vollstädt-Klein et al, 2011), and reaction time studies (Oliver & Drobes, 2012) that found attentional bias toward CIG compared to neutral images among non-smokers. One reason for this universal bias could be that the cigarette cues were less complex visual stimuli than the neutral stimuli (i.e., all of cigarette pictures contained a cigarette, while the neutral pictures were of varying content), but other work suggests that LPPs to picture stimuli are sensitive to motivational relevance but not stimulus complexity (Bradley, Hamby, Löw, & Lang, 2007; Franken, Van Strien, Bocanegra, & Huijding, 2011). Another reason could be that cigarette stimuli were primed because of experimental demand effects (i.e., participants were all recruited into a study advertised as being smoking-related).…”
Section: Discussionmentioning
confidence: 99%
“…The P3 component is thought to reflect controlled processing and has been shown to correspond to the motivational relevance of emotional stimuli [33]. The greater P3 amplitude for negative words at baseline then likely reflects controlled, sustained attention and elaboration of negative self-referential information.…”
Section: Discussionmentioning
confidence: 99%
“…The P2 component reflects automatic monitoring of semantic meaning [26]. In this context, modulation of the P3 has been shown to correspond to the motivational relevance of emotional stimuli [33], and likely reflects controlled processing of the stimuli. The early and late LPP also reflect controlled cognitive processing of the emotional words [26], but the early LPP (< 600 ms) may also be sensitive to changes in the stimulus [37].…”
Section: Introductionmentioning
confidence: 99%